Penggunaan Media Sosial Youtube Sebagai Sarana Dalam Menyampaikan Berita Pada Media YouTube Jabar Ekspres - Sahira, Zahra; Enjang; Darsono, Dono (Annaba: Jurnal Ilmu Jurnalistik, 2025)
This research aims to analyze the use of YouTube social media as a means of conveying news by Jabar Ekspres, a regional news media in West Java. In the digital age and changing media landscape, platforms like YouTube have become important tools for news organizations to reach and engage with increasingly diversified audiences. The research method used in this research is a qualitative descriptive study. Data was collected through observation, interviews with production team members, and content analysis of news videos uploaded on the Jabar Ekspres YouTube channel. The collected data was then analyzed to identify issue selection, news presentation, and evaluation of news content used by Jabar Ekspres on their YouTube channel. This research provides a deeper understanding of how regional news media such as Jabar Ekspres use YouTube social media as a tool to convey news. The results of this research can be a basis for improving news presentation strategies in the ever-growing digital era, and are relevant for the development of the news media industry.